Megalastrum oppositum and Ctenitis canacae (Dryopteridaceae): A new combination and a new synonym, respectively, for Mascarene fern flora - Duan, Yi-Fan; Zhang, Libing (Phytotaxa, 2014)
We synonymized Ctenitis canacae with C. opposita (basionym: Aspidium oppositum) and proposed a new combination, Megalastrum oppositum. We also lectotypified Aspidium oppositum.